Analisis Faktor Konfirmatori dalam Mengukur Kapasitas Target Pasar Kredit Usaha Mikro, Kecil, dan Menengah - Syti Sarah Maesaroh (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
This study aims to examine and analyze the determinants of the MSME's low absorption of bank credit. The determinant variables observed were business characteristics, management administration, resources, and performance of MSMEs. Each of these factors consists of several indicators that play a role in determining the capacity of MSMEs. The research analysis method uses confirmatory factor analysis (CFA) to confirm the effect of each indicator. The results showed that all the indicators tested had a significant effect on the absorption rate of MSME's credit products. The indicators that have the most role in determining the capacity of MSMEs were the level of use of their capital, the availability of financial reports, and the level of education of business actors. Banking strategies related to these three factors focused on increasing MSME credit absorption. Optimizing credit absorption is expected to improve performance in banks and MSMEs